Spin-polarized oscillations of conductance through an Aharonov-Casher ring with a quantum gate - 黄豪 施耀铭 宋红岩 张爱芳 (Journal of Shanghai University, 2006)
Spin-polarized oscillations in conductance is studied through a mesoscopic Aharonov-Casher （AC） ring with a quantum gate that is tuned by an external magnetic field. Both the conductance and its spin polarization at zero temperature are calculated as a function of the textured electric field, the magnetic field, and Fermi energy. It is found that for some special Fermi energies, spin-up electrons are driven into perfect transmission or reflection states, unaffected by the electric field when Zeeman energy of the incident electrons aligns with one level of the isolated stub or is larger than Fermi energy. This brings about AC oscillations of spin-down conductance. It shows that periodic oscillations of the conductance appear in the adiabatic region of quantum phase and in the normdiabatic region. Anomalous behavior of the conductance oscillation is dependent on the difference between the tilt angle of spin and the electric field.